Rapid progression of condyloma acuminatum caused by IL-17A antibody treatment: a case report - Sun, Fang; Yu, Zhenze (Frontiers in Medicine, 2024)
Anti interleukin (IL)-17A therapy is a common and effective treatment for psoriasis, but there are also risks of infection. In this case, we presented a patient who experienced a swift progression of condyloma acuminatum on the genitals during psoriasis treatment with secukinumab, a human IL-17A antagonist. Through this case, we strongly suspect that anti IL-17A treatment may promote the onset and rapid progression of low-risk HPV-associated condyloma acuminatum.